Design of channel wing using lifting line theory and particle swarm optimization - Wong, Jun Ta; Abdul Hamid, Mohd Faisal (The Aeronautical and Astronautical Society of the Republic of China, 2024)
The present work studies the optimization of the channel wing design to increase the lift coefficient. The model of the channel wing is constructed using the lifting line theory (LLT), which has been validated through a crossvalidation study against experimental wind tunnel results. This model is then applied as the fitness function for the design optimization process, which is performed using the particle swarm optimization (PSO) method. For this study, several design parameters of the channel wing are considered to be varied to obtain their optimal settings. Based on the results of the optimization process, it has been found that the optimal channel length should constitute approximately 28.7% of the semi-wing span with a taper ratio of 0.63. Compared with the original CCW-5, the optimized channel wing has a higher lift coefficient (+48.65%), which holds significant potential for short takeoff and landing. The optimization results also suggest to have a slight twist in the channel wing along with a considerable amount of wing incidence angle. Furthermore, the case study involving a 20% increase in parameters indicates that wing span, length from the root chord to the channel and wing setting angle positively affect the lift coefficient.